Lithium Salt Dissociation in Diblock Copolymer Electrolyte Using Fourier Transform Infrared Spectroscopy - Kim, Kyoungmin; Kuhn, Leah; Alabugin, Igor V.; Hallinan, Daniel T. (Frontiers in Energy Research, 2020)
Polymer electrolytes are important materials in the manufacture of all-solid-state batteries due to their ionic conductivity, achieved by doping the polymer with salt, and mechanical strength, achieved by use of a block copolymer with a rigid block. High salt concentration is advantageous to achieve high ionic conductivity, but it makes estimation of battery performance difficult due to the breakdown of dilute-solution theory, which assumes complete ion dissociation. Therefore, practical battery design would benefit from an empirical understanding of the relationship between ion dissociation and salt concentration in block copolymer electrolyte. In this study, the dissociation of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in polystyrene (PS) – poly(ethylene oxide) (PEO) diblock copolymer electrolyte was investigated using Fourier transform infrared (FTIR) spectroscopy. Quantitative analysis was performed to reveal the appearance of ion pairs and interactions between the salt and the ethylene oxide moieties with increasing salt concentration. FTIR peaks associated with polymer functional groups were found to be more useful than those of the TFSI anion for understanding the chemical state of the block copolymer electrolyte. In particular, PS peaks were used to quantify polymer dilution upon salt addition and verify that the Beer-Lambert law was valid at all concentrations investigated. PEO peaks revealed conformational changes of the polymer upon coordination with lithium ions. A previously unidentified FTIR peak was discovered that relates to polymer-salt interaction. It was used to determine the extent of salt dissociation, which compares well with a Raman study of a homopolymer electrolyte. This work definitively shows that LiTFSI dissolves into the PEO phase of the block copolymer, essentially unaffected by PS presence. It also establishes FTIR as a useful technique for quantifying dissociation state of concentrated polymer and composite electrolytes for lithium batteries.